(untitled) (Wardah, 2019)
Abstract: Since Malaysia got its independence around 60 years, it has known as a country which had a plural society not even the variety of language but also the variety of religiousity and ethnic. This has shown that the plurality in Malaysia has been a long time. Unfortunately, in facing this plural society seems difficult for some Muslims in Malaysia because of lacking knowledge in terms of approaching dan communicating with this group. Hence, the objective of an article is to review the Islamic responses regarding on the functions of comparative religion in confronting the plural society in Malaysia. The methodology of this article is basically qualitative which focusing on the literatures. The findings showed that comparative religion is important for Malay Muslim to learn and understand more about other people in Malaysia. Keywords: Comparative religion, plural society, Malaysia